2015
DOI: 10.1080/02772248.2015.1041526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physico-chemical properties and metal contents of water and sediments of Bodo Creek, Niger Delta, Nigeria

Abstract: Some physico-chemical properties and the concentrations of the metals Fe, Mn, Ni, Cd, Cr, Co, Cu, Pb, and Zn in water and sediments were examined from September 2011 to January 2012 in Bodo Creek, where oil spills have been recurrent. Temperature, pH, total dissolved solid, conductivity, salinity, dissolved oxygen, biological oxygen demand (BOD), chemical oxygen demand (COD), total hardness, sulfate, nitrate, and phosphate were determined in surface water. Particle size, total organic matter (TOM), and pH were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 12 publications
(18 reference statements)
6
21
2
Order By: Relevance
“…This implies that the linear model was significant, and there was a strong correlation and the implication was that Co, in sediment increased with increase in Co content of clam. These results are in concomitant with those reported by [21,22].…”
Section: Characteristics Of Surficial Sediment Qualitysupporting
confidence: 92%
“…This implies that the linear model was significant, and there was a strong correlation and the implication was that Co, in sediment increased with increase in Co content of clam. These results are in concomitant with those reported by [21,22].…”
Section: Characteristics Of Surficial Sediment Qualitysupporting
confidence: 92%
“…Increases in pH may be caused by acceleratedalgal growth, such as that which may occur during an algal bloom (when pH canexceed 10) and denitrification. Lower wet season pH values for the rivers water were found to be consistent with the findings reported by many workers [3,18,19,20,29].…”
Section: River Water Physico-chemical Parameterssupporting
confidence: 92%
“…Chemical contaminants or pollutants in the aquatic environment can be divided into four groups, viz: the plant nutrients, the oxygen consuming substances, the inorganic substances including some anions and heavy metals; and the organic compounds. While the first two groups are not directly harmful to aquatic life, the last two groups especially the heavy metals and most organic compounds constitute the environmental refectories (not usually eliminated from the environment by natural degradation) and with direct toxicity to aquatic life [19,24,29]. Of particular concern to environmental toxicologists are those compounds, which accumulate in the tissues, from often undetectable concentrations in water; organisms may accumulate levels of biological significance (bioaccumulation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[73] They reported significant increase in metal (zinc, lead and copper) loads postspill. A follow-up study [74] on metal concentrations in water and sediment in Bodo Creek also reported concentrations of magnesium, iron, copper, zinc, chromium, lead and cobolt as being higher than the World Health Organization [58] recommended permissible levels for surface and drinking water.…”
Section: Impact On Freshwater Ecology In the Niger Deltamentioning
confidence: 99%